Prevalence and pattern of self-medication among undergraduate medical students in various medical colleges in Kashmir: a student initiated research - Dar, Abdul Hamid; Fareed, Zeshan; Bhagat, Anshika; Jan, Iqra; Khan, Zahid Ali; Qureshi , Uruj (International Journal Of Community Medicine And Public Health, 2024)
Background: Self-medication is a widespread practice among medical students, often driven by their growing medical knowledge and easy access to drugs. This study aims to determine the prevalence and pattern of self-medication practices among undergraduate medical students in various medical colleges of Kashmir. Methods: A cross-sectional study was conducted among 218 undergraduate medical students from three medical colleges in Kashmir. Data were collected using a structured questionnaire to assess demographic characteristics, self-medication prevalence, reasons for self-medication, and types of drugs used. Statistical significance was set at p<0.05. Results: Of the 218 participants, 152 (69.7%) were female, and 66 (30.3%) were male. The mean age of participants was 21±1.56 years. The prevalence of self-medication was 49%, with final-year students showing the highest prevalence (52%), followed by first-year students (28.4%). Headaches (55%) and rhinitis (44%) were the most common reasons for self-medication. Analgesics (33%) and antibiotics (29%) were the most frequently used drugs. While 68% of students were aware of the risks associated with self-medication, only 3.8% reported experiencing adverse events. Conclusions: Self-medication is highly prevalent among medical students in Kashmir, especially among senior students. The frequent use of antibiotics raises concerns about antimicrobial resistance. Educational interventions are needed to promote rational drug use and reduce unsafe self-medication practices.